PEMBERDAYAAN KWT SEJAHTERA DALAM PEMANFAATAN TANAMAN HERBAL DI PEKARANGAN RUMAH UNTUK MENJAGA IMUN TUBUH KELUARGA - GH, Muliana; Arsal, Andi Faridah; Yusuf, Yusnaeni; Khalidatunnisa, Besse; Ainun, Nur Aisyah (Program Studi Manajemen FEB UNM, 2025)
This community service activity aimed to empower the Kelompok Wanita Tani (KWT) Sejahtera in Kabba Village, Minasate’ne Sub-district, Pangkep Regency, in utilizing herbal plants grown in their home yards as a means to strengthen family immunity. The implementation method consisted of three stages: preparation, implementation, and evaluation. The preparation stage involved observation and interviews to identify suitable herbal plant potentials. The implementation stage included outreach, training, and demonstrations on cultivating and processing herbal plants into immunity-boosting remedies. Evaluation was conducted through pre- and post-training questionnaires. The results showed a significant increase in participants' knowledge and awareness of the benefits of herbal plants, with 75% of KWT members starting to plant and use herbal plants independently. This activity successfully promoted a healthy lifestyle based on local resources and supported efforts to enhance family resilience in a sustainable manner. The program is expected to serve as an environmentally friendly community empowerment model that contributes to the achievement of Sustainable Development Goals (SDGs), particularly in the areas of health and well-being.